Alkali Activation of Oil Shale Ash Based Ceramics - A. Hamadi; K. Nabih (E-Journal of Chemistry)
Timahdit oil shale was subjected to firing transformation via ceramics processing followed by alkali activation to synthesis a materials combining the mechanical properties of ceramics and Zeolites. The mineralogical transformations during firing oil shale have been studied. The main crystalline phases found in oil shale ash (OSA) were wollastonite, gehlenite and augite. Modified oil shale ash (MOSA) was obtained with HNO3 acid-leaching in the aim to diminish Ca content. Our experimental approach required a NaOH alkaline activating solution with different concentrations (0.5; 1; 2; 4; 6 and 8M). In our study, X-ray diffraction (XDR), Fourier transform infrared (FTIR) and SEM/EDS analysis were used to evaluate the effect of alkali activation on the structural arrangement of the starting materials (OSA and MOSA) in our study. The quantity and the type of the produced zeolites depended critically on the starting materials and on the NaOH concentration.